Pakistan : Report on the Observance of Standards and Codes (ROSC)-Data Module. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This Report on the Observance of Standards and Codes (ROSC) provides a review of Pakistan's data dissemination practices against the IMF's General Data Dissemination System (GDDS), complemented by an in-depth assessment of the quality of the national accounts, consumer and wholesale price indices, and government finance, monetary, and balance-of-payments statistics. Pakistani authorities are strongly committed to adhering to internationally accepted standards and good practices, as demonstrated by their recent participation in the GDDS. Nevertheless, the mission identified shortcomings in some statistical practices and databases.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet